Project scheduling with limited resources using an efficient differential evolution algorithm - Behrouz Afshar-Nadjafi; Hamid Karimi; Amir Rahimi; Somayeh Khalili (Journal of King Saud University. Engineering sciences, 2015)
Extensive research has been devoted to resource constrained project scheduling problem (RCPSP). Resources are renewable and there is a unique way to perform the activities. This work develops a population based evolutionary algorithm namely differential evolution (DE) to schedule project activities to minimize makespan subject to precedence constraints and resources availability. The proposed DE uses a priority value based representation to encode a project schedule and a serial generation scheme to obtain the schedule. The DE algorithm is compared with some existing algorithms available in the literature on the basis of a computational experiment performed on Patterson’s test bed. Obtained results show that the performance of the proposed DE is quite satisfactory.